038 Tremor: a clinical and neurophysiological study. (29th July 2019) - Fois, Alessandro; Mahant, Neil; Vucic, Steve; Fung, Victor SC
Abstract : Introduction: Tremor is a common clinical problem seen in a number of diseases. Robust classification and diagnosis of tremor remains controversial due to overlap in clinical features and lack of established biomarkers. This hampers effective research including therapeutic trials. We present our research protocol for a cross-sectional study which aims to find more robust methods of tremor classification and diagnosis. Methods: Adults with upper limb tremor of varying aetiologies, diagnosed using current clinical criteria (including essential tremor, Parkinsonian tremor, and dystonic tremor), and age-matched controls are eligible for recruitment. Participants undergo a clinical and neurophysiological assessment, including accelerometry, surface electromyography, long-latency stretch reflexes, temporal discrimination, and tonic vibration reflexes. Data will be analysed using a cluster analysis to identify robust tremor syndromes and biomarkers associated with them. We aim to recruit 100 participants prior to analysis. Results: At time of writing, 13 participants with upper limb tremor have been studied (6 with essential tremor, 5 with dystonic tremor, and 2 with indeterminate tremor; mean age 66 years, range 18–85). Participants tolerated the clinical and neurophysiological studies well with 100% completion rate after recruitment. With current rates of recruitment we anticipate completion of recruitment and commencement of data analysis in October 2019. Conclusions: Our protocol aims to identify robust tremor phenotypes and biomarkers for them. This will allow patients with tremor to be classified into more biologically homogeneous diagnostic categories, aiding future research into the mechanism of tremor and more rational clinical trial design.